Metals and Their Workers: Our Thundering Cannon - Porter, Gerald (Tautosakos darbai, 2020)
Iron and steel have been the backbones of Wales, Scotland, Ireland and England for many centuries. This paper includes three growing case studies: itinerant tinkers in Ireland in the Middle Ages, the setting up of an ironworks in the Black Country in the English Midlands and in Wales from 1784, and a strike in a steel mill in Scotland in 1986. Around them grew a song culture which included 1) songs of revolt, 2) cultural sayings and 3) (one) paean to the ironmasters. Even the simplest songs discussed here can be regarded as dismantling the barriers between work, the raw material, and the wider social and political life of the workers. The later songs take up a stance and assert a place to stand, and characteristically the position of the singers offers resistance to authoritarian and life-denying attitudes. Significantly, there is as yet little evidence that in the iron and steelworks the songs were sung at work as they were in, for example, Ulster’s linen mills. However, there is recent evidence that the songs have been sung in both solo and in unison, a practice that has been emphasised in recent research in other fields (Korczynski, Pickering, Robertson 2013; Porter 2018a, 2018b). Singing in the arduous conditions of an industrial workplace, a pub or on a demonstration in this way can be called performing a role, a way in which singers have asserted their sense of unity as well as unison. In fact, songs for individual singers which were actually performed by iron and steelworkers are often even harder to find, and have usually been written by outsiders and in recent times.